Online Student Team Achievement Division (STAD) Learning Model on Nursing Competency Test Ability - Kaluku, Suratno; Hariawan, Hamdan; Tatisina, Cut Mutia; Ningsih, Mira Utami (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2024)
The COVID-19 pandemic also has an impact on the transition from conventional education to digital education. Digital learning requires software as a medium during the learning process. Currently, the most widely used media in teaching nursing practice is social media in the form of WhatsApp and Telegram. The effectiveness of the implementation of cooperative learning, one of which is the STAD model in improving the quality of learning. The purpose of conducting research on improving the ability of nursing students in answering various Competency Test questions through the STAD model approach by utilizing social media WhatsApp. This study was a quasi-experimental study (quasi-experimental) with a research design in the form of a pre-posttest design with a control group (pretest-posttest control design) involving two groups, namely the treatment group and the control group. Both were given a pretest, and a posttest about learning the STAD method with WhatsApp media and was given an intervention. The study was conducted on July 14 to September 27, 2021 as many as 60 people. The results of the study stated that there was a significant difference in the ability to answer questions about the research subjects of the intervention and control groups in learning through WhatsApp online media (p <0.05). The increase in the average delta ability to answer competency test questions with the STAD method is better than without going through the STAD method, with d value of 56.95.